The Effect of Lower-Limb Exercise on Pain Management of the Patients Undergoing Posterior Lumbar Fusion Surgery: A Retrospective Case-Control Study - Tong Wu; Yong Ye (Pain Research and Management)
Purpose. The purpose of this study is to investigate the clinical effect of lower-limb exercise, when combined with celecoxib, on pain management of patients undergoing posterior lumbar fusion surgeries. Methods. The patients undergoing posterior lumbar fusion surgeries between 01/2018 and 06/2021 were retrospectively identified, with their data collected. After surgery, some patients took celecoxib for analgesia (celecoxib group, 200 mg/day) while the others took celecoxib together with lower-limb exercise (combined group, celecoxib-200 mg/day). On postoperative days (POD) 1, 3, 7, and 14, data were collected and analyzed regarding the following items: patient satisfaction, lower-limb muscle force, lumbar JOA score (29 points), Oswestry Disability Index (ODI), and visual analog scale (VAS) score. Results. A total of 225 participants were included in this study. Specifically, 120 cases were admitted into in the celecoxib group and 105 were included in the combined group. Comparisons of baseline data did not indicate any difference between the combined group and the celecoxib group. Data analysis showed that patient satisfaction in the combined group was significantly higher than the celecoxib group on POD 3, 7, and 14, respectively (all p<0.001). Moreover, the combined group had less VAS score compared with the celecoxib group on POD 3, 7, and 14, respectively (all p<0.01). In addition, lower-limb muscle force in the combined group was significantly stronger than that in the celecoxib group on POD 3 and POD 7, respectively (both p<0.01). Furthermore, the combined group achieved less ODI score than the celecoxib group on POD 3, 7, and 14, respectively (all p<0.05). Comparisons of the lumbar JOA score did not suggest any statistical difference during the whole follow-up period. Conclusions. In conclusion, postoperative lower-limb rehabilitation exercise can help to release pain after lumbar fusion surgeries. Additionally, postoperative lower-limb exercise can facilitate the recovery of lower-limb muscle force, as well as improving patient satisfaction.